EVALUASI KEBIJAKAN PROSEDUR PENGAWASAN DAN PENGENDALIAN KAWASAN MANGROVE DI WILAYAH KOTA SURABAYA (Studi Kasus Evaluasi Dampak Peraturan Walikota Surabaya no. 65 Tahun 2011 di Kelurahan Wonorejo, Kota Surabaya) - Lunariana Lubis (Faculty of Social and Political Science, 2015)
The coastal region is a potential resource in Indonesia, which is a transitional region between land and sea. Surabaya as a seaside town is one example of how local governments should respond to the adverse impacts of coastal ecosystem destruction that will worsen the carrying capacity of coastal areas that are naturally highly susceptible to damage due to environmental changes and natural disasters. Especially the east coast of Surabaya which has become a special attention in nature conservation which aims to minimize the impact of environmental changes and natural disasters. One of nature conservation in east coast of Surabaya is conservation of mangrove forest. The condition of Mangrove Forest in Pamurbaya from year to year continues to be degraded. Illegal logging for the opening of ponds, settlements, recreation or timber is the cause of destruction of mangrove forests in Pamurbaya. Monitoring policy and control of mangrove area is a policy made to protect and conserve mangrove area. Surabaya City Government has issued Perwali number 65 of 2011 which contains policy of monitoring and controlling procedures of mangrove area in Surabaya City area. The scope of this Perwali is socialization, community empowerment, monitoring and evaluation, investigation and reporting. Implementation of this research has a purpose to know and analyze the impact of Mayor of Surabaya Regulation No. 65 of 2011 on procedures for monitoring and controlling mangrove area in the area of Surabaya. This research use desciptive qualitative approach. Some methods used in order to determine and collect data in this study are Observation, Interview (Interview), and Documentation. The stages of data analysis in this study is Data collection (Data collecting), Presentation of data (Data display), and Conclusion. This research uses qualitative approach with phenomenology research type, where in phenomenology research emphasize on phenomenon to be explored based on single concept or idea point of view (Creswell, 2013) Impact of Mayor of Surabaya Regulation No. 65 of 2011 on procedures for monitoring and controlling mangrove areas in the area of Surabaya city is running well but the city government surabaya should always increase supervision and supervise the successful implementation of the mayoral regulations. Socialization of affected communities must be sustainable and continuously done until the creation of a sense of ownership and preservation of the community around the mangrove forest independently.